النموذج التجريمي لجريمة حرمان الأنثى من الميراث في القانون الليبي - د. أبوبكر امحمد أحمد احتيوش (Sharwes Scientific Journal, 2025)
The crime under investigation is established by its two elements (material and moral) under Law No. (6) of 1959 regarding the protection of women’s inheritance rights. It reflects an issue of legislative deficiency. The researcher concluded.